Screen-viewing behaviours of children before and after the 2020-21 COVID-19 lockdowns in the UK: a mixed methods study - Ruth Salway; Robert Walker; Kate Sansum; Danielle House; Lydia Emm-Collison; Tom Reid; Katie Breheny; Joanna G. Williams; Frank de Vocht; William Hollingworth; Charlie Foster; Russell Jago (BMC, 2023)
Abstract Background Restrictions during the COVID-19 pandemic have led to increased screen-viewing among children, especially during strict periods of lockdown. However, the extent to which screen-viewing patterns in UK school children have changed post lockdowns is unclear. The aim of this paper is to examine how screen-viewing changed in 10-11-year-old children over the 2020-21 COVID-19 pandemic, how this compares to before the pandemic, and the influences on screen-viewing behaviour. Methods This is a mixed methods study with 10-11-year-olds from 50 schools in the Greater Bristol area, UK. Cross-sectional questionnaire data on minutes of weekday and weekend television (TV) viewing and total leisure screen-viewing were collected pre-COVID-19 in 2017-18 (N = 1,296) and again post-lockdowns in 2021 (N = 393). Data were modelled using Poisson mixed models, adjusted for age, gender, household education and seasonality, with interactions by gender and household education. Qualitative data were drawn from six focus groups (47 children) and 21 one-to-one parent interviews that explored screen-viewing behaviour during the pandemic and analysed using the framework method. Results Total leisure screen-viewing was 11% (95% CI: 12%-18%) higher post-lockdown compared to pre-COVID-19 on weekdays, and 8% (95% CI: 6%-10%) on weekends, equating to around 12-15 min. TV-viewing (including streaming) was higher by 68% (95% CI: 63%-74%) on weekdays and 80% (95% CI: 75%-85%) on weekend days. Differences in both were higher for girls and children from households with lower educational attainment. Qualitative themes reflected an unavoidable increase in screen-based activities during lockdowns, the resulting habitualisation of screen-viewing post-lockdown, and the role of the parent in reducing post-2020/21 lockdown screen-viewing. Conclusions Although screen-viewing was higher post-lockdown compared to pre-COVID-19, the high increases reported during lockdowns were not, on average, sustained post-lockdown. This may be attributed to a combination of short-term fluctuations during periods of strict restrictions, parental support in regulating post-lockdown behaviour and age-related, rather than COVID-19-specific, increases in screen-viewing. However, socio-economic differences in our sample suggest that not all families were able to break the COVID-19-related adoption of screen-viewing, and that some groups may need additional support in managing a healthy balance of screen-viewing and other activities following the lockdowns.